Consumer behavior - Berkman, Harold W.; Lindquist, Jay D.; Sirgy, M. Joseph (Lincolnwood, Ill. : NTC Business Books, 1997)
This book is divided into five sections: The Consumer in the Marketplace; The Consumer as Decision Maker; Psychological Influences on Consumer Decision Making; Sociological Influences on Consumer Decision Making; and The Consumer in Society.
Keywords: Consumer behavior; Consumer behavior